Solid waste aggregate anti-freezing concrete and preparation method thereof
By enhancing the treatment of solid waste aggregate and optimizing the water reducing agent and gas-induced agent in the concrete formula, the structural damage problem of anti-freeze concrete under the freeze-thaw cycle is solved, and efficient solid waste resource utilization is achieved. Improved concrete performance.
Patent Information
- Application Number
- CN202411693525.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Existing frozen-resistant concrete is prone to structural damage under the freeze-thaw cycle, resulting in irreversible permanent damage to the project quality. In addition, solid waste aggregates are prone to form weak areas when used in concrete, reducing frost resistance.
By enhancing the solid waste aggregate, the solid waste aggregate is soaked with calcium chloride, potassium carbonate and other components in the enhancer to enhance its density and structural strength, and combined with water reducing agent and gas induction agent Use, adjust the internal structure and bubble distribution of concrete to improve freezing resistance.
It realizes efficient resource utilization of solid waste aggregate anti-freeze concrete, improves the compressive strength and freezing resistance of concrete, reduces the consumption of natural aggregates and the pollution of solid waste materials, and has the characteristics of green and environmental protection.
Smart Images

Figure BDA0005151577780000071 
Figure BDA0005151577780000072 
Figure BDA0005151577780000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to solid waste aggregate frost-resistant concrete and a preparation method thereof. Background Art
[0002] Frost resistance is an important indicator for evaluating the durability of concrete. Performance degradation and damage of concrete buildings in cold regions under freeze-thaw cycles are the main diseases during their use. Therefore, more and more concrete structure designs have frost resistance grade requirements. This kind of concrete that requires long-term resistance to freeze-thaw cycles is generally called frost-resistant concrete.
[0003] The reason why concrete is required to have a certain degree of frost resistance is that, on the one hand, when the temperature is between 0 and 4°C, the hydration reaction of cement is extremely slow. After water freezes into ice, there is not enough liquid water in the concrete to participate in the hydration reaction of cement. The strength growth of concrete is extremely slow or even stops, and the strength development of concrete cannot meet the requirements. On the other hand, when the temperature is below 0°C, most of the water inside the concrete is frozen, and when water freezes into ice, it expands by about 9%. Under the action of this expansion stress, a large pressure will be generated on the capillary pores inside the concrete. When the temperature rises, the ice gradually melts into water, and this pressure is released. Under the repeated action of this pressure, the concrete structure is gradually damaged, and over time it will suffer permanent damage.
[0004] As environmental pollution becomes increasingly serious, how to promote the green and low-carbon development of the building materials industry has become a common concern of all sectors of society. As one of the most widely used building materials, concrete has an increasing demand and waste volume, and aggregate accounts for the vast majority of it. Using solid waste to prepare aggregates can not only effectively reduce the consumption of natural raw materials of sand and stone in the concrete production process, thereby reducing damage to the ecological environment, but also achieve the recycling of solid waste. However, during the production process, solid waste aggregates have the characteristics of many internal initial defects, large porosity, and high water absorption. When solid waste aggregates are used to make concrete, it is easy to cause more connected harmful pores to form inside the concrete, resulting in large defects in the transition zone of the concrete interface and easy formation of weak areas. When the external temperature and humidity change and the concrete undergoes freeze-thaw cycles, the concrete is prone to structural damage under the repeated effects of water freezing expansion pressure and ice dissolution release pressure, which in turn leads to irreversible permanent structural damage to the quality of the project. Summary of the invention
[0005] The main purpose of the present invention is to provide a solid waste aggregate frost-resistant concrete and a preparation method thereof in view of the problems and shortcomings of the prior art. The obtained frost-resistant concrete has good mechanical properties and freeze-thaw resistance, and has a high content of solid waste materials, thereby achieving efficient resource utilization of solid waste materials, reducing the consumption of natural aggregates, being green and environmentally friendly, and having important application prospects.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] Provided is a solid waste aggregate antifreeze concrete, characterized in that the components and their weight proportions include: 170-340 parts of ordinary Portland cement, 40-120 parts of fly ash, 40-170 parts of mineral powder, 10-40 parts of vanadium-titanium slag powder, 900-1100 parts of coarse aggregate, 800-1000 parts of sand, 160-180 parts of water, and 3-20 parts of admixture;
[0008] Wherein: coarse aggregate includes common coarse aggregate and reinforced waste ceramic aggregate, the mass percentage of the reinforced waste ceramic aggregate in the coarse aggregate is 0-100%; sand includes common machine-made sand and reinforced nickel slag sand, the mass percentage of the reinforced nickel slag sand in the sand is 0-100%; the contents of the reinforced waste ceramic aggregate and the reinforced nickel slag sand are not the same at the same time, which is 0;
[0009] The waste ceramic aggregate and nickel slag sand are respectively soaked in an aqueous solution of a reinforcing agent in advance for reinforcing treatment; the reinforcing agent comprises, by mass percentage, 2-5% calcium chloride, 3-6% potassium carbonate, 30-40% methanol, 50-60% triisopropanolamine and 0.2-1.0% nanofibrillated cellulose;
[0010] The admixture is an aqueous solution formed by a composite of a water reducing agent and an air entraining agent.
[0011] According to the above scheme, the mass percentage of the waste ceramic aggregate after the reinforcement treatment in the coarse aggregate is 50-100%; the mass percentage of the nickel slag sand after the reinforcement treatment in the fine aggregate is 50-100%.
[0012] According to the above scheme, the mass percentage concentration of the aqueous solution of the enhancer is 15-30%.
[0013] According to the above scheme, the reinforcing agent is prepared by uniformly dispersing nanofibrillated cellulose in methanol and triisopropanolamine and then adding calcium chloride and potassium carbonate and stirring.
[0014] Preferably, the nanofibrillated cellulose is added to methanol and triisopropanolamine and dispersed evenly using ultrasonic dispersion method.
[0015] According to the above scheme, the waste ceramic aggregate or nickel slag sand is immersed in the aqueous solution of the reinforcing agent for 16 to 36 hours.
[0016] According to the above scheme, the weight proportion of the admixture in the solid waste aggregate antifreeze concrete is 10 to 20 parts.
[0017] According to the above scheme, the CaO content of the ordinary Portland cement is ≥65%, the 45μm negative pressure sieve residue is ≤30%, and the specific surface area is 300-500m 2 / kg, 28d compressive strength ≥42.5MPa.
[0018] According to the above scheme, the fly ash 45μm negative pressure sieve residue is ≤45%, the water requirement ratio is ≤115%, and the strength activity index is ≥70%.
[0019] According to the above scheme, the 28d activity index of the mineral powder is ≥80%, and the fluidity ratio is ≥90%.
[0020] According to the above scheme, the vanadium-titanium slag powder has a 45 μm negative pressure sieve residue of ≤45%, a water requirement ratio of ≤115%, and a strength activity index of ≥60%.
[0021] According to the above scheme, the particle size of the ordinary coarse aggregate is 5-31.5 mm, which meets the continuous grading requirement, the mud powder content is ≤1.5%, the water absorption rate is ≤1.0%, the needle and flake particle content is ≤10%, and the crushing value is ≤25%.
[0022] According to the above scheme, the particle size of the ordinary machine-made sand is 0-5 mm, the fineness modulus is 2.6-3.2, the stone powder content is ≤15%, the MB value is ≤2.0, and the crushing value is ≤25%.
[0023] According to the above scheme, the waste ceramic aggregate is made from discarded ceramics through crushing and screening. The particle size of the waste ceramic aggregate is 5-31.5 mm, meets continuous grading, the crushing value is ≤25%, the water absorption rate is ≤3%, and the micro powder content is ≤2%.
[0024] According to the above scheme, the nickel slag sand is made by crushing and screening the remaining waste ore after nickel-iron ore sorting, with a particle size of 0-5mm, a fineness modulus of 2.6-3.2, a micro powder content of ≤10%, an MB value of ≤3.0, and a crushing value of ≤25%.
[0025] According to the above scheme, in the admixture, the components are 10-40% of water reducing agent, 2-10% of air entraining agent, and 50-80% of water, calculated by mass percentage.
[0026] According to the above scheme, in the admixture, the water reducer is one or more of polycarboxylic acid water reducer, naphthalene water reducer, aliphatic water reducer, melamine water reducer, aminosulfonic acid water reducer. Preferably, the solid content of the water reducer is 30-60%, and the water reduction rate is 20-50%.
[0027] According to the above scheme, in the admixture, the air entraining agent includes 10-30% rosin soap, 3-18% rosin thermal polymer, 50-85% sodium dodecylbenzene sulfonate and 0.3-2% ethylene glycol dimethacrylate by mass percentage.
[0028] A method for preparing the above-mentioned solid waste aggregate frost-resistant concrete is provided, comprising the following steps:
[0029] 1) The waste ceramic aggregate and nickel slag sand are respectively soaked in an aqueous solution of a reinforcing agent in advance for reinforcing treatment;
[0030] 2) ordinary Portland cement, fly ash, mineral powder, vanadium-titanium slag powder, ordinary coarse aggregate, ordinary machine-made sand, the waste ceramic aggregate after the reinforcement treatment in step 1) and nickel slag sand are mixed and stirred evenly, then water is added and stirred evenly, and finally the compounded admixture is added and stirred evenly to obtain solid waste aggregate antifreeze concrete.
[0031] According to the above scheme, in step 1), the soaking time is 16 to 36 hours.
[0032] According to the above scheme, in step 2), the mixing time of the powder and aggregate is 5 to 15 seconds; the mixing time after adding water is 15 to 30 seconds; and the mixing time after adding the admixture is 1 to 2 minutes.
[0033] The present invention provides a solid waste aggregate antifreeze concrete, which uses solid waste aggregate to replace natural sand and stone aggregate. However, the surface of the solid waste aggregate is rough, the pores are large, and the water absorption rate is high. The use of the solid waste aggregate to prepare concrete will form a weak area at the interface between the new and old aggregates, resulting in many internal defects of the concrete, increased porosity, and poor compactness, thereby reducing the antifreeze performance of the concrete. The present invention uses a reinforcing agent to enhance the solid waste aggregate; wherein the calcium chloride and potassium carbonate in the reinforcing agent can react to generate fine calcium carbonate particles, and nanofibrillated cellulose can be adsorbed on the surface of the particles to avoid the aggregation and precipitation of calcium carbonate particles, which is conducive to the calcium carbonate particles to better fill the surface gaps of the solid waste aggregate, making the solid waste aggregate structure more compact, and the structure is enhanced, so that the antifreeze performance of the concrete is improved. In addition, the size of nanofibrillated cellulose is relatively fine, much smaller than the particle size of cement-based materials, which enables it to enter the gel pores, capillary pores and micropores between the hydration product CSH gel of the cement matrix, make up for the nano-scale defects of the cement matrix, reduce the total porosity, and refine the pore size distribution, thereby improving the density of the cement matrix, and then improving the interface strength of the concrete, so that the frost resistance of the concrete is improved.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention provides a solid waste aggregate antifreeze concrete, which uses solid waste aggregate to replace natural sand and gravel aggregate, and strengthens the solid waste aggregate. The internal defects of the solid waste aggregate are repaired to a certain extent, harmful pores are significantly reduced, and the remaining pores are mostly harmless pores. During the freeze-thaw cycle, a part of the expansion pressure of external water caused by freezing will be released internally, so that the frost resistance of the concrete is improved; combined with other components, the obtained concrete has high compressive strength and good frost resistance, and the solid waste material content is high, which realizes efficient resource utilization of solid waste materials, can effectively reduce the development of natural sand and gravel aggregates, reduce the pollution caused by the solid waste materials themselves, is green and environmentally friendly, and has important application prospects.
[0036] 2. Furthermore, an air entraining agent is added to the water reducing agent. The rosin soap, rosin thermal polymer, sodium dodecylbenzene sulfonate and ethylene glycol dimethacrylate in the air entraining agent can effectively increase the number of bubbles, enrich the range of bubble sizes, and prolong the existence time of bubbles, thereby adjusting the bubble size and enhancing the bubble strength, so that the bubbles can better block the capillary passages, and can also release the ice crystal expansion pressure in the capillaries during the freezing process, thereby effectively improving the freeze-thaw resistance of concrete. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] In the following examples, the raw material indicators used are as follows:
[0039] Ordinary Portland cement has a CaO content of 67%, a 45μm negative pressure sieve residue of 16.8%, and a specific surface area of 362m 2 / kg, 28d compressive strength 49MPa.
[0040] The fly ash 45μm negative pressure sieve residue is 25.5%, the water requirement ratio is 96%, and the strength activity index is 81%.
[0041] The 28d activity index of the mineral powder is 97% and the fluidity ratio is 102%.
[0042] The vanadium-titanium slag powder has a 45μm negative pressure sieve residue of 27%, a water requirement ratio of 108%, and a strength activity index of 69%.
[0043] Ordinary coarse aggregate is crushed stone with a continuous grading of particle size from 5 to 31.5 mm, a mud powder content of 1.2%, a water absorption rate of 0.8%, a needle-shaped and flaky particle content of 7.8%, and a crushing value of 11%.
[0044] The particle size of ordinary machine-made sand is 0-4.75 mm, the fineness modulus is 2.9, the stone powder content is 8%, the MB value is 0.5, and the crushing value is 16.7%.
[0045] Waste ceramic aggregate is made from discarded ceramics through crushing and screening, with a particle size of 5 to 31.5 mm in continuous grading, a crushing value of ≤18.3%, a water absorption rate of 2.6%, and a micro powder content of 1.7%.
[0046] Nickel slag sand is the waste ore remaining after nickel-iron ore sorting, which is processed by crushing and screening. It has a particle size of 0-4.75mm, a fineness modulus of 3.0, a micro powder content of 6%, an MB value of 2.0, and a crushing value of 22%.
[0047] The admixtures, by mass percentage, are composed of 20% water reducer, 2% air entraining agent, and 78% water; of which:
[0048] The water reducer used is a compound of polycarboxylic acid water reducer and aminosulfonic acid water reducer in a mass ratio of 1:2. The solid content and water reduction rate are 30%, 40% and 40%, 50% respectively. The reagents are purchased from the market.
[0049] The air entraining agent is prepared by compounding rosin soap, rosin thermal polymer, sodium dodecylbenzene sulfonate and ethylene glycol dimethacrylate in the proportions of 10%, 15%, 74.5% and 0.5%. The rosin soap component is sodium rosinate, the rosin thermal polymer component is rosin phenol resin, and the reagents are purchased from the market.
[0050] The reinforcing agents calcium chloride, potassium carbonate, methanol, triisopropanolamine, and nanofibrillated cellulose were purchased from the market. Nanofibrillated cellulose is a type of nanocellulose, generally obtained by treating plant fibers by chemical-physical methods. As a reinforcing material, it can promote cement hydration, increase the density of cement-based materials, and improve their mechanical properties and durability.
[0051] The present application is further described in detail below in conjunction with the embodiments. The specific concrete mix ratios are shown in Table 1.
[0052] Comparative Example 1
[0053] A solid waste aggregate antifreeze concrete, the preparation method of which comprises the following steps: cement, fly ash, mineral powder, vanadium titanium slag powder, common crushed stone, common machine-made sand, water, and admixture are weighed respectively according to Table 1, the powder and aggregate are first stirred for 10 seconds to be evenly mixed, then water is added and stirred for 15 seconds, and finally the compounded admixture is added (the admixture composition is shown in the specific embodiment part, the same below), and then stirred for 2 minutes. A concrete mixture can be obtained.
[0054] Comparative Example 2
[0055] A solid waste aggregate antifreeze concrete, the preparation method of which comprises the following steps: cement, fly ash, mineral powder, vanadium titanium slag powder, nickel slag sand, common crushed stone, water, and admixture are weighed respectively according to Table 1, the powder and aggregate are first stirred for 10 seconds to mix evenly, then water is added and stirred for 15 seconds, and finally the compounded admixture is added and stirred for 2 minutes. A concrete mixture can be obtained.
[0056] Comparative Example 3
[0057] A solid waste aggregate antifreeze concrete, the preparation method of which comprises the following steps: weigh cement, fly ash, mineral powder, vanadium titanium slag powder, common machine-made sand, waste ceramic aggregate, water, and admixture according to Table 2.1, first stir the powder and aggregate for 10 seconds to mix evenly, then add water and stir for 15 seconds, finally add the compounded admixture, and stir for 2 minutes. A concrete mixture can be obtained.
[0058] Comparative Example 4
[0059] A solid waste aggregate antifreeze concrete, the preparation method of which comprises the following steps: cement, fly ash, mineral powder, vanadium titanium slag powder, nickel slag sand, waste ceramic aggregate, water, and admixture are weighed respectively according to Table 1, wherein the admixture does not contain an air entraining agent component. First, the powder and the aggregate are stirred for 10 seconds to mix evenly, then water is added and stirred for 15 seconds, and finally the compounded admixture is added and stirred for 2 minutes. A concrete mixture can be obtained.
[0060] Example 1
[0061] A solid waste aggregate frost-resistant concrete, the preparation method of which comprises the following steps:
[0062] The nickel slag sand is reinforced in advance with a reinforcing agent, which is a compound of calcium chloride, potassium carbonate, methanol, triisopropanolamine, and nanofibrillated cellulose in the proportions of 3.5%, 4%, 32%, 60%, and 0.5%. The mixture is then mixed for 30 minutes to make it uniformly mixed. Finally, water is added to form an aqueous solution with a mass percentage concentration of 25%. The mixture is stirred evenly and allowed to stand for 1 hour. Waste ceramic aggregate or nickel slag sand is then added thereto and soaked for 20 hours for reinforcement treatment. The water is then drained for later use.
[0063] Then, cement, fly ash, mineral powder, vanadium-titanium slag powder, nickel slag sand, crushed stone, water, and admixtures were weighed according to Table 1, and the powder and aggregate were stirred for 10 seconds to mix evenly, and then water was added and stirred for 15 seconds, and finally 10 parts of the compounded admixture were added and stirred for another 2 minutes. The antifreeze concrete mixture was obtained.
[0064] Example 2
[0065] A solid waste aggregate frost-resistant concrete, the preparation method of which comprises the following steps:
[0066] The waste ceramic aggregate is reinforced with a reinforcing agent in advance, and the reinforcing agent is a compound of calcium chloride, potassium carbonate, methanol, triisopropanolamine, and nanofibrillated cellulose at 3.5%, 4%, 32%, 60%, and 0.5%, and then mixed for 30 minutes to make it evenly mixed. Finally, water is added to make a 25% mass percentage concentration aqueous solution, stirred evenly and left to stand for 1 hour, and then the waste ceramic aggregate or nickel slag sand is added thereto and soaked for 20 hours for reinforcement treatment, and then the water is drained for standby use.
[0067] Then, cement, fly ash, mineral powder, vanadium-titanium slag powder, machine-made sand, reinforced waste ceramic aggregate, water, and admixtures were weighed according to Table 1, and the powder and aggregate were stirred for 10 seconds to mix evenly, and then water was added and stirred for 15 seconds, and finally 10 parts of the compounded admixture were added and stirred for another 2 minutes. The antifreeze concrete mixture was obtained.
[0068] Embodiment 3-5
[0069] A solid waste aggregate frost-resistant concrete, the preparation method of which comprises the following steps:
[0070] The nickel slag and waste ceramic aggregate are reinforced with a reinforcing agent in advance, wherein the reinforcing agent is calcium chloride, potassium carbonate, methanol, triisopropanolamine, and nanofibrillated cellulose in the proportions of 3%, 4%, 32%, 60%, and 1%, and then mixed for 30 minutes to make the mixture uniform. Finally, water is added to form a 30% mass concentration aqueous solution, which is stirred evenly and allowed to stand for 1 hour, and then the waste ceramic aggregate or nickel slag is added thereto and soaked for 20 hours for reinforcement treatment, and then the water is drained for later use.
[0071] Then, cement, fly ash, mineral powder, vanadium-titanium slag powder, machine-made sand, reinforced nickel slag sand, crushed stone, reinforced waste ceramic aggregate, water, and admixture were weighed according to Table 1, and the powder and aggregate were stirred for 10 seconds to mix evenly, and then water was added and stirred for 15 seconds, and finally 12 parts of the compounded admixture were added and stirred for 2 minutes. The antifreeze concrete mixture was obtained.
[0072] Embodiment 6-8
[0073] A solid waste aggregate frost-resistant concrete, the preparation method of which comprises the following steps:
[0074] The nickel slag and waste ceramic aggregate are reinforced with a reinforcing agent in advance, wherein the reinforcing agent is calcium chloride, potassium carbonate, methanol, triisopropanolamine, and nanofibrillated cellulose in the proportions of 3%, 4%, 32%, 60%, and 1%, and then mixed for 30 minutes to make the mixture uniform. Finally, water is added to form a 30% mass percent aqueous solution, which is stirred evenly and allowed to stand for 1 hour, and then the waste ceramic aggregate or nickel slag is added thereto and soaked for 20 hours for reinforcement treatment, and then the water is drained for later use.
[0075] Then, cement, fly ash, mineral powder, vanadium-titanium slag powder, machine-made sand, reinforced nickel slag sand, crushed stone, reinforced waste ceramic aggregate, water, and admixture were weighed according to Table 1, and the powder and aggregate were stirred for 10 seconds to mix evenly, and then water was added and stirred for 15 seconds, and finally 12, 15, and 20 parts of the compounded admixture were added respectively, and the amount of admixture was further increased, and then stirred for 2 minutes. The antifreeze concrete mixture can be obtained.
[0076] The antifreeze concretes of Comparative Examples 1 to 4 and Examples 1 to 7 were tested for mechanical properties and antifreeze properties, respectively. The results are shown in Table 2.
[0077] Table 1. Proportions of frost-resistant concrete obtained in Comparative Examples 1 to 4 and Examples 1 to 7 (kg / m 3 )
[0078]
[0079] Table 2. Performance test of frost-resistant concrete obtained from Comparative Examples 1 to 4 and Examples 1 to 7
[0080]
[0081]
[0082] It can be seen from Table 1 and Table 2 that:
[0083] In comparative example 1, the concrete prepared with pure natural aggregate has higher 28d compressive strength and relative dynamic elastic modulus after freeze-thaw cycles than the concrete with solid waste aggregate added. This is because the surface of solid waste aggregate is rough and porous, and there are large cracks. These cracks can absorb a certain amount of water. During the freeze-thaw cycle, the internal structure of the concrete is easily damaged due to the pressure generated by the expansion of water freezing. Therefore, the strength and frost resistance are lower than those of natural sand and gravel aggregate concrete.
[0084] Compared with Example 1, and Example 2, the strength and frost resistance of concrete are improved after being strengthened with nickel slag sand or waste ceramic aggregate. This is because cracks and defects are easily generated on the surface of solid waste aggregates during production and preparation. After the solid waste aggregates are strengthened, the strengthened products can fill the surface cracks, optimize internal defects, and make the structure denser, so the strength and frost resistance are improved.
[0085] Examples 3, 4, 5, and 6 show that the concrete prepared by strengthening nickel slag sand and waste ceramic aggregates and combining them with natural sand and gravel aggregates still has high strength and frost resistance, and the performance gradually improves with the increase in the amount of strengthened solid waste aggregates. This is because strengthening nickel slag sand and waste ceramic aggregates is beneficial to the strength and frost resistance of concrete. At the same time, when combined with natural sand and gravel aggregates, the grading of concrete aggregates is optimized, making the concrete structure more compact, further improving the strength and frost resistance of concrete.
[0086] Compared with Examples 6, 7, and 8, in Comparative Example 4, after strengthening nickel slag sand and waste ceramic aggregate, the dosage of the admixture is further increased, and the strength and frost resistance of the concrete are improved. This is because the air entraining component in the water reducer is increased, and the small bubbles introduced by the air entraining agent cut off the passage of the capillary, thereby improving the compactness of the concrete. These micropores can also release the expansion pressure of ice crystals in the capillary during the freezing process, thereby avoiding the generation of destructive pressure and reducing the destructive effect of freeze-thaw, thereby increasing the strength and frost resistance of the concrete.
[0087] The above results show that the solid waste aggregate concrete prepared in Examples 1 to 8 has high compressive strength and good frost resistance; the use of solid waste aggregate in the preparation not only reduces the consumption of natural aggregate, but also increases the recycling of solid waste and reduces the damage to land and groundwater resources caused by its storage.
[0088] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.
Claims
1. A solid waste aggregate frost-resistant concrete, characterized in that: The components and their weight proportions include: 170-340 parts of ordinary Portland cement, 40-120 parts of fly ash, 40-170 parts of mineral powder, 10-40 parts of vanadium-titanium slag powder, 900-1100 parts of coarse aggregate, 800-1000 parts of sand, 160-180 parts of water, and 3-20 parts of admixture; wherein: The coarse aggregate includes ordinary coarse aggregate and reinforced waste ceramic aggregate, and the mass percentage of the reinforced waste ceramic aggregate in the coarse aggregate is 0-100%; the sand includes ordinary machine-made sand and reinforced nickel slag sand, and the mass percentage of the reinforced nickel slag sand in the sand is 0-100%; the contents of the reinforced waste ceramic aggregate and the reinforced nickel slag sand are not the same at the same time, and are 0; The waste ceramic aggregate and nickel slag sand are respectively soaked in an aqueous solution of a reinforcing agent in advance for reinforcing treatment; the reinforcing agent comprises, by mass percentage, 2-5% calcium chloride, 3-6% potassium carbonate, 30-40% methanol, 50-60% triisopropanolamine and 0.2-1.0% nanofibrillated cellulose; The admixture is an aqueous solution formed by a composite of a water reducing agent and an air entraining agent.
2. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The mass percentage concentration of the enhancer in the aqueous solution of the enhancer is 15-30%.
3. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The waste ceramic aggregate or nickel slag sand is immersed in the aqueous solution of the reinforcing agent for 16 to 36 hours.
4. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The weight proportion of the admixture in the solid waste aggregate antifreeze concrete is 10 to 20 parts.
5. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The mass percentage of the waste ceramic aggregate after the reinforcement treatment in the coarse aggregate is 50-100%; the mass percentage of the nickel slag sand after the reinforcement treatment in the sand is 50-100%.
6. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The ordinary Portland cement has a CaO content of ≥65%, a 45 μm negative pressure sieve residue of ≤30%, and a specific surface area of 300-500 m 2 / kg, 28d compressive strength ≥42.5MPa; The fly ash has a 45 μm negative pressure sieve residue of ≤45%, a water requirement ratio of ≤115%, and a strength activity index of ≥70%; The mineral powder has a 28d activity index of ≥80% and a fluidity ratio of ≥90%; The vanadium-titanium slag powder has a 45 μm negative pressure sieve residue of ≤45%, a water requirement ratio of ≤115%, and a strength activity index of ≥60%; The particle size of the ordinary coarse aggregate is 5 to 31.5 mm, meets the continuous grading requirement, has a mud powder content of ≤1.5%, a water absorption rate of ≤1.0%, a needle and flake particle content of ≤10%, and a crushing value of ≤25%; The particle size of the common machine-made sand is 0-5 mm, the fineness modulus is 2.6-3.2, the stone powder content is ≤15%, the MB value is ≤2.0, and the crushing value is ≤25%.
7. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The particle size of the waste ceramic aggregate is 5 to 31.5 mm, meets continuous grading, has a crushing value of ≤25%, a water absorption rate of ≤3%, and a micro powder content of ≤2%; The nickel slag sand has a particle size of 0-5 mm, a fineness modulus of 2.6-3.2, a micro powder content of ≤10%, an MB value of ≤3.0, and a crushing value of ≤25%.
8. The solid waste aggregate frost-resistant concrete according to claim 1, characterized in that: The admixture comprises, by mass percentage, 10-40% of a water reducing agent, 2-10% of an air entraining agent, and 50-80% of water; wherein the air entraining agent comprises 10-30% of rosin soap, 3-18% of rosin thermal polymer, 50-85% of sodium dodecylbenzene sulfonate, and 0.3-2% of ethylene glycol dimethacrylate.
9. The solid waste aggregate frost-resistant concrete according to claim 1 or 8, characterized in that: Among the admixtures, the water reducer is one or more of a polycarboxylic acid water reducer, a naphthalene water reducer, an aliphatic water reducer, a melamine water reducer, and an aminosulfonic acid water reducer.
10. A method for preparing solid waste aggregate frost-resistant concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: 1) The waste ceramic aggregate and nickel slag sand are respectively soaked in an aqueous solution of a reinforcing agent in advance for reinforcing treatment; 2) ordinary Portland cement, fly ash, mineral powder, vanadium-titanium slag powder, ordinary coarse aggregate, ordinary machine-made sand, the waste ceramic aggregate after the reinforcement treatment in step 1) and nickel slag sand are mixed and stirred evenly, then water is added and stirred evenly, and finally the compounded admixture is added and stirred evenly to obtain solid waste aggregate antifreeze concrete.
Citation Information
Patent Citations
Nano modified inorganic mineral waterproof agent as well as preparation method and application thereof
CN114163159A
Anti-freezing high-ductility composite material as well as preparation method and application thereof
CN114163192A
Modification material for low-quality aggregate and treatment method
WO2022041374A1